Current Strategies and Novel Therapeutic Approaches for Metastatic Urothelial Carcinoma - Mollica, Veronica; Rizzo, Alessandro; Montironi, Rodolfo; Cheng, Liang; Giunchi, Francesca; Schiavina, Riccardo; Santoni, Matteo; Fiorentino, Michelangelo; Lopez-Beltran, Antonio; Brunocilla, Eugenio; Brandi, Giovanni; Massari, Francesco (Cancers, 2020)
Urothelial carcinoma (UC) is a frequent cause of cancer-related deaths worldwide. Metastatic UC has been historically associated with poor prognosis, with a median overall survival of approximately 15 months and a 5-year survival rate of 18%. Although platinum-based chemotherapy remains the mainstay of medical treatment for patients with metastatic UC, chemotherapy clinical trials produced modest benefit with short-lived, disappointing responses. In recent years, the better understanding of the role of immune system in cancer control has led to the development and approval of several immunotherapeutic approaches in UC therapy, where immune checkpoint inhibitors have been revolutionizing the treatment of metastatic UC. Because of a better tumor molecular profiling, FGFR inhibitors, PARP inhibitors, anti-HER2 agents, and antibody drug conjugates targeting Nectin-4 are also emerging as new therapeutic options. Moreover, a wide number of trials is ongoing with the aim to evaluate several other alterations and pathways as new potential targets in metastatic UC. In this review, we will discuss the recent advances and highlight future directions of the medical treatment of UC, with a particular focus on recently published data and ongoing active and recruiting trials.